Domination in the intersection graphs of rings and modules - Heidar Jafari, Sayyed; Jafari Rad, Nader (Italian Journal of Pure and Applied Mathematics, 2011)
In this paper we obtain domination number in the intersection graphs of ideals of rings, and intersection graphs of submodules of modules.